Censusing Asian Elephants by Dung Density Count in Mayurbhanj Elephant Reserve of Odisha, India - Swain, Debabarata; Behura, Basanta Kumar (Indian Forester, 2013)
The Mayurbhanj Elephant Reserve is located between 21°10' to 22°35' North latitude and 85°45'to 87°05' East 2 longitude, spreading over 7043.74 km in Mayurbhanj, Balasore, Bhadrak and Keonjhar districts of Odisha state (India). It comprises of a continuous tract covering Similipal Tiger Reserve, Kuldiha Sanctuary, Hadgarh Sanctuary and other Reserved Forest, Protected Forest, Village Forest, Revenue and homestead land. As part of the MIKE/CITES programme, elephant census based on dung density count was taken up in the Reserve during January to May, 2005. The paper presents the methodology adopted and findings of this census. The Reserve was divided into high, medium, low, and no elephant usage strata based on elephant census of 2002 (total count method). Based on dung-pile abundance on the ground, defecation rate, and dung decay rate, the final estimate of elephant numbers was made for each stratum. The dung density count of elephants shows that there are at least 788 elephants in the Reserve.